The Miser as seen by the director Oliver Frljić – the issues of (re)affirmation of theatre’s social function - Gospić Županović, Ana (Molière u hrvatskoj kulturi, 2024)
Different, even experimental stagings of Molière as a world classic are a constant choice in the repertoire of many theatres in Europe, including Croatia, especially national theatres. In this paper, starting from the wellknown tradition of directorial readings or adaptations by which Molière’s best-known works were brought into different contexts and adapted, the play The Miser directed and dramatized by Oliver Frljić, performed in 2009 and produced by Croatian National Theatre in Rijeka, is presented, and analysed. With regard to the basic elements of the play, the ways and modalities of the author’s recontextualization of this classic text are explored, which are created in the tradition of more radical political readings and adaptations of Molière in the contemporary context, and aesthetically in the wake of Brecht’s epic modus and in the context of the issue of re(affirmation) of the social function of the theatre.